Maranhão Crisálida? Práticas discursivas e rede de relações sociais no governo de José Sarney 1966/1970 - Pereira, Robison Raimundo Silva (2008)
This research shows the speech importance of the candidate to Maranhão government José Sarney and his political ability with the central power, the local social strenth, the press and a past time of glory, as he says. These actions of a political life in society do not refer to the politician s individual actions only. They also refer to the collective action in a clear relation of the politician with a global social historic context. This work gives us possibilities of a worldwide vision on a developing concept and policy application in the search of economical environment centrality, according to a general vision of this concept. Relevant arguments about this subject are presented, going from its conceptual difference and its unsustainable application in governmental policy through a long last speech in Maranhão. This investigation identifies the alliances set in a government named Maranhão Novo , the relations among public and private, political, economical and social individuais involved, joined in the practicing of squatting whose interdependent relations happen in a certain social historic moment. In the end, such actions and relations have confirmed deep changes in economics and maranhense society. Meanwhile planners and the fact that the development is feasible strictly economical, were forgotten, bringing an enormous concentration of lands. This consequent constitution of land owners, motivated by central government policy, with the national integration speech, a new age of captalism in the state began.